Currículo integrado do PROEJA: concepção e orientação pedagógica - SANTOS, Natália Cristina Goiabeira dos (2018)
The present Master Thesis is part of the research group “Escola, Currículo, e Formação Docente of the Postgraduate Course on Education at Federal University of Maranhão. We analyze on this research the Integrated Curriculum of PROEJA from Curso Técnico em Comércio on Campus IFMA-Bacabal on its theoretical and methodology fundamentals. The methodology approach that this research bases, it is the qualitative approach because it allow to analyze the object from the context that it belong in a macro and micro perspective, make possible as well the critical dialectic about the reality that the object belongs. The authors we use are: Lessard-Hérbert et al (1990), Kosik (1976), Gamboa (1998) (2010). The instrument use for data collection was the semi structure interview with teachers, coordinator and director. The sample research was compound by six teachers, one coordinator form EJA and a director that works on Campus – IFMA Bacabal. The theoretical fundamentals that bases our work are the following authors: Gramsci (2001), Arroyo (2016), Bernstein (1990), Freire (1996), Lopes and Macedo (2011), Silva (2016), Ramos (2007), Gallo (2000), Lück (1994), Fleuri (2003), Frigotto (2005), Frigotto, Ciavata and Ramos (2011), Di Pierro and Haddad (2000), Cavalieri (2010), Garcia and Ferreira (2012), so, as well the Laws and Decrees that are the bases for PROEJA: the Documento Base of PROEJA (2007), Decree nº 5458/2006, Resolutions and Internal Rules of IFMA, the Plano de Curso from the Curso Técnico em Comércio Campus IFMA-Bacabal (2017). When we analyze the data collection we conclude that the Plano de Curso of Curso Técnico em Comércio do not contemplate the conception of integrated curriculum that is propose on Documento Base of PROEJA. That Document defends an omnilateral and holistic formation that prepare the students to understand and act critically on the reality that they are include. Actually, the Plano de Curso is center on skills and competency that try to prepare the students on a medium term to be available for the market. We also detected that the teachers who works on Curso Técnico em Comércio do not have in depth knowledge about the PROEJA program and others do not even know the program, as well they do not have contact with the Documento Base. It was revealed that, though the teachers acknowledge the principles that guide the program, those same teachers show some sensibility to understand what is integrated curriculum. Because of this, they show the necessity of formation.